Avaliação do ciclo de vida de materiais de construção produzidos com fibras vegetais cultivadas no Brasil – sisal, juta e malva - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
To demonstrate the environmental impacts generated by products, from the extraction of the raw materials to their final disposal, there is a scientifically accepted tool known as life cycle assessment (LCA). Besides the technical performance, the objective of this study was to evaluate the environmental performance of composite materials, in this case cementitious plates produced with vegetable fibers grown in Brazil, namely sisal, jute and malva. The study used 1 m2 of composite plate to enable the modeling of a theoretical production chain and the use of the LCA tool. Using the ReCiPe 2016 Midpoint/Endpoint and EN 15804 methods, the environmental performance of cementitious plates has been studied under different scenarios. Firstly, as an alternative to composites produced with a Portland cement matrix, a composite with a geopolymeric matrix based on residue and reinforced with sisal fibers was developed. The durability of this composite was evaluated through wetting and drying cycles, because the longer the useful life of a material, the more significant its environmental benefits will be. Then, the environmental performance of the geopolymeric composite was compared to that of a composite with a Portland cement matrix, both materials being reinforced with sisal fibers. Using the ReCiPe 2016 Midpoint/Endpoint and EN 15804 methods, the results were convergent: the composite with cementitious matrix has a lower environmental impact. In the composite with the cementitious matrix, the cement production and the transportation process were responsible for most of the environmental load. In the geopolymeric composite, the results showed that the alkaline activator based on potassium hydroxide is the most impactful component, followed by the transport process. Considering that transporting raw materials over long distances increases the environmental burden of the products, it was inferred that, from the environmental point of view, it would be more advantageous to produce the composite with cementitious matrix replacing the sisal fibers, which are grown in the Brazilian Northeast, by the fibers of jute and malva, which are grown in the Brazilian Amazon, where this study was conducted. In this context, the fibers of jute and malva were evaluated as a reinforcement of the composite from two perspectives: one without processing and the other in the form of a fabric. Thus, it was found that if the fibers were used without any processing, being obtained from a city near Manaus, the reduction of impact related to the reinforcement of the composite would be over 95%. Thus, this research contributes scientifically by presenting potential alternatives to the construction industry that have already been evaluated from an environmental perspective.
Keywords: Juta - Amazônia; Malva - Amazônia; Fibras vegetais; Materiais de construção; ENGENHARIAS: ENGENHARIA CIVIL: CONSTRUCAO CIVIL: MATERIAIS E COMPONENTES DE CONSTRUCAO; Avaliação do ciclo de vida; Sustentabilidade; Sisal; Juta; Malva; Materiais de construção; Economia circular